Mazzini - Mack Smith, Denis 1920-2017 (Yale Univ. Press, 1994)
Giuseppe Mazzini was one of the outstanding figures in the political history of nineteenth-century Europe. A vigorous proponent of nationalism, pre-eminent figure in the struggle for Italian independence and unity, and fascinating personality, his ideas were influential throughout Europe. Yet successive Italian governments, fearing the consequences of his belief in democracy and revolution, deliberately obscured his achievements: there have been few modern studies of Mazzini, and no biography in English since 1902. Denis Mack Smith's major new account re-examines Mazzini's ideological impact and his place in the political and intellectual world of the mid-nineteenth century. Based on profound scholarship and immense archival research, the book vividly re-creates Mazzini's long years of poverty and exile in London, and the networks of friends, associates and enemies that brought him into contact with the greatest European figures of the age, among them Marx, Carlyle, Mill, and Bakunin. Mazzini is revealed as an acute but largely unrecognised prophet of the idea of a European community: he saw nationalism as a step towards larger and more harmonious confederations. Adept at inspiring animosity, as well as admiration, Mazzini affronted the pope by his demand for religious reform, Karl Marx by his powerful critique of communism, and many of his less enlightened contemporaries by his campaigns on behalf of social security, universal suffrage, and women's rights. Yet he was universally venerated for his brilliance, humanity and wisdom, and even his critics agreed that he left an enduring mark on his time.
Keywords: Mazzini, Giuseppe <1805-1872>; Mazzini, Giuseppe -- 1805-1872; Hommes d'État - Italie - Biographies; Révolutionnaires - Italie - Biographies; Geschichte; Revolutionaries -- Italy -- Biography; Statesmen -- Italy -- Biography; Italie - Histoire - 1815-1870; Italië; Italien; Italy -- History -- 1815-1870; Biografie